Elementos chave para a construção de observatórios de CT&I : conceitos, serviços, indicadores e fontes de informação - Macêdo, Diego José (2020)
The dynamics between Science, Technology and Innovation (STI) is increasingly important and complex, having a direct impact on social welfare. The measurement of activities is used as an instrument for evaluation and comparison between sectors and countries that wish to understand these relationships through the indicators. Observatories come increasingly being employed within the study of social sciences and therefore are created for better understanding of the dynamics in STI. Thus, comprise elements which are arranged in the structure of STI observatories is a starting point to begin this discussion. However, there are still gaps to be explored, especially when observing the concepts presented and the structuring of STI observatories, especially those that are being implemented in digital environments. Thus, the objective of the study is to present the structural elements of digital STI observatories, considering the concept, services, indicators and information sources used, in order to propose relevant elements for this type of informational environment. The approach is qualitative with descriptive purposes, using data collection as a method for collecting and analyzing content for analysis of the five sites of STI observatories. The research results showed that the empirical concept of the observatory is aligned with the Information Science and monitoring of STI; the main information sources are secondary from agencies and national and international databases; services ranging from policy studies and strategies in STI to interactive platform for viewing indicators; and the production and supply of various indicators, highlighting the input and output, are the basis of STI observatories.